STUDY OF MICROALBUMIN IN TYPE 2 DIABETES MELLITUS WITH LESS THAN AND MORE THAN FIVE YEARS OF DURATION. - DR. B. JYOTHIRMAYI (International Journal of Pharma and Bio Sciences, 2014)
Presence of microalbumin in type 2 diabetes mellitus patients is early sign of onset of microvascular complications which can damage various organs like heart, kidneys, eyes and nervous system. The principal aim of the study is to compare the microalbumin levels with duration of diabetes. The study was conducted in 30 diabetic subjects with less than 5 years of duration and more than 5 years of duration as controls and subjects respectively. .Microalbuminuria was considered to be positive when 24 hrs urine sample contains 30 to 300mg /g of creatinine. Biochemical analysis was done using commercially available kit for plasma glucose (GOD-POD method), lipid profile - cholestrol by enzymatic method, triglycerides by glycerol kinase method, HDL by enzymatic method, VLDL and LDL by Friedwalds calculated method and Serum creatinine by Jaffes method. Microalbumin was measured using commercially available kit by immunoturbidimetric method. The mean fasting blood sugar, cholesterol, triglycerides and microalbumin levels are high in subjects compared to controls (p<0.001). Systolic blood pressure was also high in subjects compared to controls. The duration of diabetes also showed significant association with microalbumin levels (p<0.001).